Manejo forestal con bases científicas - Gadow, Klaus von; Sánchez Orois, Sofía; Aguirre Calderón, Oscar Alberto (Instituto de Ecología, A.C., 2016)
Forests are complex open systems with multiple functions. To maintain high standards and credibility among the public, forest managers need to draw on the expertise of a variety of scientific disciplines, including the humanities, the physical, the engineering and biological sciences, not necessarily in that order. It is often postulated that forest management should be sustainable, based on validated research results, conform to acceptable environmental standards and be transparent to the public. These objectives can be met a) if various silvicultural options are compared using validated research results, b)  if management practices are understandably demonstrated in the field, and c) if management activities are effectively monitored, considering a variety of ecological conditions. Based on these premises, a practical framework for the management of a forested landscape includes three elements: Forest Options Design, Research and Demonstration and Harvest Event Analysis. The objective of the paper is to present a framework for science-based management of a forested landscape, which includes these three elements.